Clinical Profile and Non-invasive Predictors of Fibrosis in a Newly Diagnosed Non-Alcoholic Fatty Liver Disease Patient in a Tertiary Health Care Center of Nepal (Bangladesh Medical Journal, 2024)
Non-Alcoholic Fatty Liver Disease (NAFLD) represents a spectrum of histopathologic abnormalities ranging from simple steatosis to the more aggressive non-alcoholic steatohepatitis, characterized by steatosis, parenchymal inflammation, hepatocellular ballooning and other evidence of hepatic injury. The objective of this study is to evaluate the demographic and anthropometric profile of non-alcoholic fatty liver disease and non-invasive predictors of fibrosis. This is a hospital-based observational study. A total of 280 patients were included in this study from the Department of Gastroenterology, Tribhuvan University Teaching Hospital from January 2019 to August 2021 were included. Patients presenting with non-alcoholic fatty liver disease were mostly (29.64%) of 36-45 age group. Two-third of the patients (66.78%) were asymptomatic. The mean body mass index of patients was 28.10±4.10 kg/m2 and most of them (81.07%) had body mass index >25 kg/m2. More than one third of the patients (40%) with non-alcoholic fatty liver disease had presence of metabolic syndrome. The mean (±SD) ultrasound attenuation parameter was 284.22±31.58 dB/m. Fatty liver index showed a positive and a medium strength correlation with fatty liver. On Spearman rank correlation, ultrasound attenuation parameter steatosis grading was correlated positively and strongly with the USG grading of fatty liver (p